BREEDING RESULTS OF WINTER RYE ON TOLERANCE TO DISEASES AND PRODUCTIVITY IN THE NORTH-EAST RIA - Т. К. Sheshegova; L. I. Kedrova; L. M. Shchekleina; E. I. Utkina (Зерновое хозяйство России)
The article presents the breeding results of winter rye in the North-East RIA for 64 years. The immunity and productivity of 9 released varieties, such as ‘Vyatka 2’ (1950), ‘Dymka’ (1993), ‘Kirovskaya 89’ (1993), ‘Falenskaya 4’ (1999), ‘Snezhana’ (2004), ‘Rushnik’ (2008), ‘Flora’ (2010), ‘Rada’ (2014), ‘Grafinya’ (in SVT from 2013) have been analyzed. According to the breeding methods and initial material used in the work, and the years of including of the varieties into the State Register, they have been divided into three stages of variety change and breeding having 3 varieties in each. The consistent breeding improved immunity of the varieties to snow mold, root rot and ergot. The varieties of the third stage of breeding, in comparison with the first one, showed the reduce of snow mold damage on 5,7-11,3% , their germination increased on 1,3-13,6%; root rot damage decreased from 0,30 to 0,08%, ergot damage was reduced from 3,5 to 2,6%. The most significant change in ergot damage decrease occurred among the varieties of the second and the third breeding stages. The varieties ‘Flora’, ‘Rada’, ‘Grafinya’ turned to be more tolerant to the diseases than the highly sensitive variety ‘Snezhana’. The studied varieties didn’t show any improvement in their resistance to such diseases as fusarium head blight, powdery mildew and kinds of rust. The only variety ‘Snezhana’ has shown better tolerance to rust and the variety ‘Grafinya’ turned to be less sensitive to fusarium head blight. During the breeding winter rye productivity has significantly changed.  During 9 years of study the productivity of the varieties of the first breeding stage was 4,91 t/ha, the productivity of the varieties of the second breeding stage was 5,28 t/ha, the productivity of the varieties of the third breeding stage was 5,64 t/ha. The productivity of the new varieties ‘Flora’, ‘Rada’ and ‘Grafinya’ greatly exceeds that of the previous ones. The most productive variety is ‘Rada’ with an average value of 5,72 t/ha and with a maximum one of 8,46 t/ha.